Penguatan Kompetensi Pengelola Program Malaria Melalui Pelatihan Pemetaan Reseptif - Syukri, Muhammad; Yuliawati, Yuliawati; Wardiah, Rizalia; Siregar, Sri Astuti; Butar Butar, Marta; Novitasari, Prihatini Dini; Halim, RD (Jurnal Salam Sehat Masyarakat (JSSM), 2025)
Receptive mapping is a crucial step in supporting policymakers in determining intervention priorities and formulating effective strategies in malaria control programs. Technical training on creating malaria receptive maps using the open-source application Quantum GIS (QGIS) was conducted for five staff members of the Disease Prevention and Control Division (P2P) at the Batang Hari District Health Office. The training aimed to improve participants' knowledge and skills in creating malaria receptive maps for malaria control. The training used simulation and hands-on methods, so that participants had knowledge and practical experience in map-making. Pre- and post-training evaluations were conducted using questionnaires and work products in the form of malaria receptive maps. Pre-test results showed that 60% of staff had good knowledge and practical skills in receptive mapping, while 40% showed poor understanding. After the training, all participants (100%) showed good knowledge and were able to make malaria receptive maps independently. Awareness of the importance of malaria control from the vector aspect is still uneven and needs attention in every region, especially in areas that have achieved low malaria endemicity or even free of malaria. Increased malaria mapping capacity is expected to contribute to better surveillance and control efforts at the Batang Hari Health Office.